2019
DOI: 10.5897/ajest2018.2509
|View full text |Cite
|
Sign up to set email alerts
|

Conditions of available sources of water for domestic use in selected communities in Ado-Ekiti, Ekiti State, Nigeria

Abstract: The challenges of high quality water for domestic use and particularly for potability must be overcome in its entire ramification for health and ecological environment. The aim of this study is to identify the conditions of domestic water sources in Ado-Ekiti. One water sample was drawn from the two different sources of water, that is, shallow well and Ureje River at Ureje, and two samples from one water source, that is, borehole at Ilupeju and ABUAD in Ado-Ekiti. Water samples were analyzed in the Laboratory.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It is the cheapest of the reliable drinking water sources. Studies carried out by Odeyemi et al (2013) and Oyebode et al (2019) showed that other water sources in Ekiti are exposed too much more contamination including physical, chemical and bacteriological. The quality of water tells a lot about the wellbeing of the consumer and also indirectly influences economic productivity.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is the cheapest of the reliable drinking water sources. Studies carried out by Odeyemi et al (2013) and Oyebode et al (2019) showed that other water sources in Ekiti are exposed too much more contamination including physical, chemical and bacteriological. The quality of water tells a lot about the wellbeing of the consumer and also indirectly influences economic productivity.…”
Section: Introductionmentioning
confidence: 98%
“…It is likely to be less affected than surface resources by climate variability, higher temperatures, evaporation and contamination. While the people of Ado Ekiti have access to various water sources for their domestic usage, the most sought and reliable source of drinking water is the groundwater accessed through borehole (Oyebode et al, 2019). It is the cheapest of the reliable drinking water sources.…”
Section: Introductionmentioning
confidence: 99%
“…Such examination is referred to as a geophysical survey. Study carried out by Oyebode et al (2019) showed that the major and most relied upon source of drinking water in Afe Babalola University, Ado-Ekiti, Ekiti State, Nigeria, which is the study area and for the people of her neighbouring communities is the groundwater.…”
Section: Introductionmentioning
confidence: 99%